Systematic review of anti-inflammatory agents for the management of oral mucositis in cancer patients and clinical practice guidelines - Ariyawardana, Anura; Cheng, Karis Kin Fong; Kandwal, Abhishek; Tilly, Vanessa; Al-Azri, Abdul Rahman; Galiti, Dimitra; Chiang, Karen; Vaddi, Anusha; Ranna, Vinisha; Nicolatou-Galitis, Ourania; Lalla, Rajesh V.; Bossi, Paolo; et al. (Supportive care in cancer, 2019)
Purpose The aim of this systematic review was to update the clinical practice guidelines for the use of anti-inflammatory agents in the prevention and/or treatment of oral mucositis. Methods A systematic review was conducted by the Multinational Association of Supportive Care in Cancer/ International Society of Oral Oncology (MASCC/ISOO) subcommittee on mucositis guideline update. The body of evidence for each intervention, in each cancer treatment setting, was assigned an evidence level. The findings were added to the database used to develop the clinical practice guidelines published in 2014. Based on the evidence level, one of the following three guideline determinations was possible: recommendation, suggestion, and no guidelines. Results A total of 11 new papers across five interventions were examined. The recommendation for the use of benzydamine mouthwash for the prevention of radiotherapy-induced mucositis remained unchanged. New suggestion for the use of the same for prevention of mucositis associated with chemoradiotherapy was made. No guideline was possible for any other anti-inflammatory agents due to inadequate and/or conflicting evidence. Conclusions Of the anti-inflammatory agents studied for oral mucositis, the evidence supports the use of benzydamine mouthwash in the specific populations listed above. Additional well-designed research is needed on other (class of agents) interventions and in other cancer treatment settings.